Uveitis and optic perineuritis in the context of myelin oligodendrocyte glycoprotein antibody seropositivity. (5th March 2019) - Ramanathan, S.; Fraser, C.; Curnow, S. R.; Ghaly, M.; Leventer, R. J.; Lechner‐Scott, J.; Henderson, A.; Reddel, S.; Dale, R. C.; Brilot, F.
Abstract : Background and purpose: Antibodies to myelin oligodendrocyte glycoprotein (MOG) have been identified in both children and adults with demyelination, with a strong association with bilateral or recurrent optic neuritis (ON). However, the full clinical spectrum of this newly described condition is unknown. We sought to describe non‐ON inflammatory ophthalmological presentations such as uveitis and optic perineuritis in the context of MOG antibody seropositivity. Methods: Using a live cell‐based assay analysed by flow cytometry, we identified seropositive patients referred for MOG antibody testing in Australasia between 2014 and 2017. We identified four MOG antibody‐positive patients with non‐ON inflammatory ophthalmological presentations and present their detailed clinical information in this case series. Results: Three patients had uveitis either in association with, or remote from, ON. One patient had optic perineuritis and peripheral ulcerative keratitis. We describe the presentation, examination, investigation findings and clinical course of these four patients. Conclusions: Recognition of these novel clinical associations may expand the clinical spectrum of MOG antibody‐associated presentations. An expedited diagnosis may guide the management of these complex patients.